Coupling between atmospheric layers in gaseous giant planets due to lightning‐generated electromagnetic pulses. Issue 10 (30th October 2014) - Luque, A.; Dubrovin, D.; Gordillo‐Vázquez, F. J.; Ebert, U.; Parra‐Rojas, F. C.; Yair, Y.; Price, C.
Abstract Atmospheric electricity has been detected in all gaseous giants of our solar system and is therefore likely present also in extrasolar planets. Building upon measurements from Saturn and Jupiter, we investigate how the electromagnetic pulse emitted by a lightning stroke affects upper layers of a gaseous giant. This effect is probably significantly stronger than that on Earth. We find that electrically active storms may create a localized but long‐lasting layer of enhanced ionization of up to 103 cm−3 free electrons below the ionosphere, thus extending the ionosphere downward. We also estimate that the electromagnetic pulse transports 107 J to 1010 J toward the ionosphere. There emissions of light of up to 108 J would create a transient luminous event analogous to a terrestrial "elve."